Factors influencing the use of Management Accounting Practices among SMEs in emerging economies: A case of Zimbabwe: Array - Dlamini, Banele (The Journal of Accounting and Management, 2022)
Objectives: The objective of this paper is to investigate the factors influencing the application of management accounting among Small and Medium Enterprises (SMEs) in emerging economies using Zimbabwean SMEs as a case study. The paper observed that there is lack of evidence of research-based knowledge on the factors influencing the application of management accounting among SMEs in Zimbabwe. Prior Work: Prior studies have indicated a low uptake Management Accounting Practices (MAPs) among SMEs in developing economies. Moreover, there is paltry research-based knowledge on the factors influencing the application of MAPs among SMEs in Zimbabwe. Approach: Semi-structured interviews were used to obtain data from 88 participants. Data was interpreted using qualitative content analysis. Results: Socio-economic environment, availability of funds, costs and benefits associated with the usage of management accounting, size of the organization, qualifications of accounting personnel, financial literacy of SME owners, and technology are the key determinants, according to the study. Implications: The study recommends that SME owners need to be educated on the importance of having an in-house management accountant and those who are financially unable to hire can collaborate with management accountants as business partners. The Zimbabwean government, should provide government-sponsored management accounting training to SMEs, not only in tax compilation, bookkeeping, and entrepreneurship. Additionally, the government should attend to key fundamentals that will resuscitate the economy. SMEs can utilize integrated software solutions or Microsoft Excel spreadsheets, which can enable the implementation of various management accounting tools since they cannot afford to secure management accounting software. Value: The study identified factors that influence the use of MAPs by SMEs in Zimbabwe, made recommendations for enhancing their usage and filled a knowledge vacuum in the studied area.